Access and success in higher education - Ghafar, Mohd. Najib (Penerbit UTM, 1997)
This book contains several chapters include table of content, preface, chapter 1 university success, achievement factors, internal or external factors, language proficiency, chapter 2 standardised examination, examination, chapter 3 assessment demand, assessment, learning theories, thinking skills, chapter 4 science skills and school curriculum, discovery versus expository learning, misconception in science, science and industrialisation, chapter 5 teaching task: classroom interaction, classroom research, questions and thinking process, classroom happenings, chapter 6 classroom analysis for thinking skills, instrumention, chapter 7 the first-year project, english proficiency, science proficiency, conclusion, chapter 8 epilogue, reference, appendices.